Risk factors of necrotizing enterocolitis-related mortality in preterm neonates: a preliminary prospective study - Risma Karina Kaban; Rinawati Rohsiswatmo; Ahmad Kautsar; Audesia Alvianita Sutrisno; Hardya Gustada Hikmahrachim; Nieta Hardiyanti (Paediatrica Indonesiana, 2022)
Background Necrotizing enterocolitis (NEC) is a prematurity-related complication of the gastrointestinal tract that affects 3-15% of preterm infants. Due to its atypical signs and symptoms, NEC is often diagnosed late, leading to mortality and morbidity. Objective To describe the incidence, characteristics, and survival rate of preterm infants with NEC in the Neonatal Unit of Cipto Mangunkusumo Hospital. Methods This prospective cohort study was conducted on preterm infants born in Cipto Mangunkusumo Hospital in 2019 who had NEC Bell stage 2 or higher. Subjects were recruited consecutively. NEC was classified into either early-onset (<14 days of life) or late-onset (?14 days of life). We identified the risk factors of mortality and survival using multiple Cox regression. Results Within the study period, 55/639 preterm infants born in Cipto Mangunkusumo Hospital were diagnosed with NEC. Mean gestational age was 31.16 (SD 2.63) weeks and mean birth weight was 1,378.12 (SD 438.26) grams. The median age at NEC diagnosis was 6 (range 0-24) days. The most common symptoms were gastrointestinal bleeding (29.09%) and abdominal distension (29.09%). Plain abdominal radiographs showed dilated bowels in 92.72%, thickened intestinal walls in 83.63%, and pneumatosis intestinalis in 61.81% of subjects. Positive blood cultures were found in 63.63% of subjects, with Staphylococcus epidermidis and Klebsiella pneumoniae being the predominant organisms. Median survival was 27 days and 31 days for infants born at <32 weeks and ?32 weeks gestational age, respectively (P=0.37). Median survival was 27 and 28 days in infants with early-onset and late-onset NEC, respectively (P=0.07), and 23 and 28 days in infants with birth weight of <1,000 grams and ?1,000 grams, respectively (P=0.14). Conclusion The incidence of NEC among preterm infants born in Cipto Mangunkusumo Hospital in 2019 was 8.6%. The survival rate of infants with NEC was 27.27%. Early-onset and late-onset NEC had similar mortality rates.